Wealth Allocation Framework : Dalam Kerangka Masalah - Budiantoro, Risanda A.; Fitroh Sukono Putra, Febrianur Ibnu; Chasanah, Amalia Nur (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2020)
Allah has given the guidance of Islam that can be a guide in all aspects of life including wealth management. In Islamic finance perspective, Islamic wealth allocation framework is a science issue that focuses on wealth management based on Islamic principles including Shariah maqasid. This is important, considering that as a Muslim must be able to fulfill the need to protect and preserve property (al-maal) as a manifestation of benefit. So the purpose of this study is to explain how wealth management in Islamic perspective is based on sharia maqasid concept to achieve masahah. It is expected that the results of this study can be used as a good reference for readers to better understand the Islamic wealth allocation in the future